Video-Assisted Thoracoscopic Lobectomy Versus Stereotactic Body Radiotherapy Treatment for Early-Stage Non-Small Cell Lung Cancer: A Propensity Score-Matching Analysis - Dong, Baiqiang; Zhu, Xuan; Shu, Zekai; Ji, Yongling; Lu, Fangxiao; Wang, Jin; Chen, Ming (Frontiers in Oncology, 2020)
Background Compared the overall outcomes of video-assisted thoracoscopic surgery (VATS) versus stereotactic body radiotherapy (SBRT) for stage I-II non-small cell lung cancer (NSCLC). Methods We retrospectively compared overall survival (OS), cancer-specific survival (CSS), locoregional control (LRC), and disease-free survival (DFS) at our institution between January 2012 and December 2016. Propensity score-matching was performed to reduce patient selection bias based on age, gender, Karnofsky performance score, Charlson comorbidity index, pulmonary function, and tumor diameter. Results A total of 567 patients treated with SBRT (n = 109) or surgery (n = 458) were included. Of those, 104 patients were matched for further analyses. Median follow-up was 44 months. At 3 and 5 years, OS was 88.6 and 79.9% for SBRT, and 94.2 and 91.6% for surgery (p = 0.097). There were no differences noted in 5-year CSS (83.7 vs. 91.6%, respectively; p = 0.270). The cumulative incidence of LRC at 3 and 5 years was comparable (93.5 and 93.5% vs. 94.0 and 85.9%, respectively; p = 0.621). Differences in the rates of disease-free survival at 5 years were not statistically significant (79.0 and 80.5%, respectively; p = 0.624). Conclusions This propensity score-matching analysis suggests that SBRT can be an alternative option to VATS lobectomy for stage I-II NSCLC.